Glymphatic system function in patients with newly diagnosed focal epilepsy. Issue 3 (2nd February 2022) - Lee, Dong Ah; Park, Bong Soo; Ko, Junghae; Park, Si hyung; Park, Jin‐Han; Kim, Il Hwan; Lee, Yoo Jin; Park, Kang Min
Abstract: Introduction: The aim of this study was to analyze the glymphatic system function and its relationship with clinical characteristics, global diffusion tensor imaging (DTI) parameters, and global structural connectivity in treatment‐naïve patients with newly diagnosed focal epilepsy. Methods: This retrospective single‐center study investigated patients with focal epilepsy and healthy controls. All participants underwent routine brain magnetic resonance imaging and DTI. DTI analysis along the perivascular space (DTI‐ALPS) was used to evaluate glymphatic system function. We also calculated the measures of global DTI parameters, including whole‐brain fractional anisotropy (FA), mean diffusivity (MD), axial diffusivity (AD), and radial diffusivity (RD), and performed a graph theoretical network analysis to measure global structural connectivity. Results: A total of 109 patients with focal epilepsy and 88 healthy controls were analyzed. There were no significant differences in the DTI‐ALPS index (1.67 vs. 1.68, p = 0.861) between the groups. However, statistically significant associations were found between the DTI‐ALPS index and age ( r = ‐0.242, p = 0.01), FA ( r = 0.257, p = 0.007), MD ( r = −0.469, p < 0.001), AD ( r = −0.303, p = 0.001), RD ( r = −0.434, p < 0.001), and the assortative coefficient ( r = 0.230, p = 0.016) in patients with focal epilepsy. Conclusion: The main finding of this study is that DTI‐ALPS index is significantly correlated with global DTI parameters and structural connectivity measures of the brain in patients with focal epilepsy. In addition, DTI‐ALPS index decreases with age in these patients. We conclude that the DTI‐ALPS index can be used to investigate glymphatic system function in patients with focal epilepsy. Abstract : DTI‐ALPS index is correlated with the global DTI parameters and structural connectivity of the brain in focal epilepsy. DTI‐ALPS index decreases with age in focal epilepsy patients. The DTI‐ALPS index can be used to investigate glymphatic system function in patients with focal epilepsy.